PENGARUH UKURAN PERUSAHAAN, LEVERAGE, GOOD CORPORATE GOVERNANCE, DAN VOLUNTARY DISCLOSURE TERHADAP COST OF EQUITY CAPITAL PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019 - 2023 - Angraini M, Amelia; Huda, Syamsul (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to comprehensively examine the impact of various corporate governance and financial factors—specifically company size, leverage as indicated by the Debt to Equity Ratio (DER), the presence of an independent board of commissioners, managerial ownership, institutional ownership, and voluntary disclosure—on the cost of equity capital in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. The research adopts a purposive sampling technique to select relevant companies, focusing on a population of 37 firms within this sector over the specified timeframe. Data analysis is conducted using both descriptive and verificative approaches, with hypothesis testing carried out through multiple linear regression analysis to determine the relationships between these variables and the cost of equity capitalThe results of the study reveal that company size exerts a significant partial influence on the cost of equity capital, indicating that larger companies may benefit from lower equity costs. In contrast, DER, the independent board of commissioners, managerial ownership, institutional ownership, and voluntary disclosure, when considered individually, do not significantly affect the cost of equity capital. However, when these variables are considered together, they collectively exert a significant influence on the cost of equity capital. These findings provide critical insights for corporate management and investors, emphasizing the need to consider both company size and the combined effect of governance and ownership structures when assessing the cost of equity financing in the transportation and logistics industry.  Keywords: Company Size, Leverage, Independent Board of Commissioners, Managerial Ownership, Institutional Ownership, Voluntary Disclosure, and Cost of Equity Capital.